The Hidden Role of Epstein-Barr Virus in Encephalitis: Case Studies of Diagnostic Dilemmas - Anubhav Bansal; Deepak Jain; Bharti Yadav (Българска неврология)
Epstein-Barr virus (EBV), typically associated with infectious mononucleosis and various malignancies, is an uncommon cause of encephalitis. The role of EBV in conjunction with other central nervous system (CNS) infections remains unclear, though its detection may provide critical insights into immune status and patient prognosis. This article presents three cases where EBV coexisted with primary CNS infections, complicating diagnostic and treatment processes. Case 1: A 38-year-old male with a six-month history of intermittent fever, altered sensorium, and seizures was diagnosed with disseminated tuberculosis and EBV encephalitis. Initial MRI of brain suggested viral encephalitis, and CSF analysis revealed Mycobacterium tuberculosis. CSF PCR confirmed EBV, leading to successful treatment with antiepileptics, antitubercular therapy, and acyclovir. Case 2: A 32-year-old male presented with fever, headache, vomiting, and altered sensorium. CSF analysis showed Streptococcus pneumoniae and EBV. MRI indicated extensive CNS involvement. The patient responded well to antibiotics, acyclovir, and dexamethasone. Case 3: A 47-year-old female presented with 10 days of fever, severe headache, and 2 days of altered sensorium. Examination revealed meningitis with positive Kernig’s sign. CSF PCR confirmed Mycobacterium tuberculosis and Epstein-Barr virus, and MRI showed leptomeningeal enhancement with infarcts. She responded well to antitubercular therapy, acyclovir and steroids, and was discharged in a fully conscious and oriented state.